PELATIHAN DAN PENDAMPINGAN PEMANFAATAN MEDIA DIGITAL GURU SMP MUHAMMADIYAH 1 KOTABUMI DALAM PEMBUATAN VIDEO PEMBELAJARAN - Purna Bayu Nugroho; Khusnul Khotimah; Feby Musti Ariska; Darwanto (Rafandha Press, 2023)
An educator needs to continue to develop their potential in order to support improving the quality of students in schools. One of the self-potential development activities is to participate in training activities and the development of learning videos. This activity is carried out with the aim of providing experience to teachers in training activities and assisting in making learning videos. The participants in this activity were all teachers at SMP Muhammadiyah 1 Kotabumi, North Lampung. The implementation of this activity is carried out in three stages, namely planning, implementation and evaluation. At the planning stage, the team conducts cooperation, conducts preliminary studies, and develops concepts. At the implementation stage, the team conducted training and mentoring for teachers about making learning videos. At the evaluation stage, the team evaluates the series of activities that have been carried out by conducting interviews with training participants and mentoring. This service activity was carried out from 03 August 2021 to 28 September 2021. The results of this activity were obtained in the form of 3 (three) learning videos